2005
DOI: 10.1002/biof.5520240114
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynonenal and uncoupling proteins: A model for protection against oxidative damage

Abstract: In this mini review we summarize recent studies from our laboratory that show the involvement of superoxide and the lipid peroxidation product 4-hydroxynonenal in the regulation of mitochondrial uncoupling. Superoxide produced during mitochondrial respiration is a major cause of the cellular oxidative damage that may underlie degenerative diseases and ageing. Superoxide production is very sensitive to the magnitude of the mitochondrial protonmotive force, so can be strongly decreased by mild uncoupling. Supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 83 publications
1
46
0
1
Order By: Relevance
“…The mechanism of induction of proton leak by HNE is unclear. It has been suggested that HNE may induce covalent modification and conformational changes in the UCPs that allow the passage of protons back into the mitochondrial matrix (95). Both UCP2 and 3 are expressed in the heart, but their role is unclear.…”
Section: Mitochondrial Uncoupling Proteinsmentioning
confidence: 99%
“…The mechanism of induction of proton leak by HNE is unclear. It has been suggested that HNE may induce covalent modification and conformational changes in the UCPs that allow the passage of protons back into the mitochondrial matrix (95). Both UCP2 and 3 are expressed in the heart, but their role is unclear.…”
Section: Mitochondrial Uncoupling Proteinsmentioning
confidence: 99%
“…The central nervous system is particularly vulnerable to oxidative stress, owing to its high rate of oxygen utilization and abundance of unsaturated lipids. Thus, a great deal of attention has been focussed on the possible roles of lipid peroxidation-derived aldehydes in terms of their contributions to neuronal dysfunction in oxidative stress-associated neurodegenerative disorders (25).…”
Section: Participation Of Iron Ions In the Ferritin/h2o2-mediated Lipmentioning
confidence: 99%
“…The underlying processes leading to the acute and chronic FA-induced increase in workindependent MV O 2 are far from clear. First, increased MV O 2 may be related to the following: 1) increased myocardial FA oxidation rate (accompanying the elevated FA supply), leading to increased oxygen cost due to the lower ratio of ATP produced to oxygen consumed (P/O ratio), accompanying FA oxidation (43); 2) FA and FA derivatives induce increased mitochondrial reactive oxygen species (ROS) production and activate uncoupling proteins (UCP) (15,25); and 3) FAinduced futile cycling, such as FA-triacylglycerol cycling (42). In addition, there are reasons to believe that FAs or FAmediated changes may influence Ca 2ϩ handling.…”
mentioning
confidence: 99%